Collaboration between entities and suppliers in state contracting: a need highlighted by the COVID-19 pandemic - Medina Flores, Juan Carlos (2021)
The COVID-19 pandemic has highlighted the serious problem of lack of collaboration between the parties in a public contract. The parties faced unpredictable situations and the need to make agile decisions to mitigate or reduce the impacts of the pandemic; notwithstanding, in many cases they showed conflictive behavior rather than a collaborative one that prioritizes the efficient in the contract management to achieve the attention of the emergency, the dynamism of the economy, the generation of jobs, the investment in public spending, among others. Therefore, it is important to analyze the collaboration mechanisms in public contracts that are currently available in the law, as well as those that can be implemented, without losing sight of the fact that building trust among the actors in the public procurement system is essential to align the interests of the parties and generate effective cooperative management.   The article will analyze the main concepts about contract collaboration and the different tools that can foster it.